Avian claw morphometry and growth determine the temporal pattern of archived stable isotopes. (28th January 2014) - Hahn, Steffen; Dimitrov, Dimitar; Rehse, Saskia; Yohannes, Elizabeth; Jenni, Lukas
<x xml:space="preserve">Abstract</x> Detailed knowledge about claw formation and growth rate is a prerequisite for the interpretation of avian claw stable isotopes, as is commonly done with feather stable isotopes to e.g. infer habitat use, dietary specialisations, and spatial occurrence. In this study, we provide basic information about claw formation and empirical evidence about the time scale of archiving isotopic information to develop a reliable assessment of archived isotopic pattern in claws of passerines. Avian claws grow conically from the tip of the bone of the phalanx. The length of the tip of an avian claw, suitable for stable isotope analysis, is about 42 ± 6.8% (SD) of total linear claw length and can also be estimated from the body mass of a given species. Claw growth rate in adult songbirds typically ranged between 0.03 and 0.05 mm d−1, but differed between front and back toes, and varied seasonally. From the claw growth rate, the archiving period of a given claw length can be estimated. In long‐distance migrant species, δ13C of claws matched δ13C of feathers grown during the same period (wintering or breeding period). In Palaearctic‐African migrants sampled in the breeding season, δ13C of the distal half of the claw tip reflected the African wintering site, while the proximal half reflected a blend of African and European δ13C signatures, as expected. Hence there is empirical evidence that entire claw tips mirror the isotopic environments over longer periods (up to months), and over weeks when parts can be analysed. However any part of a claw contains a blend of material formed at different times due to the claw's conical (i.e. longitudinal and lateral) growth. Avian claws provide a complementary isotope archive for investigations, but its applicability may vary according to the ecology of the study species.